Leishmania infantum amastigotes trigger a subpopulation of human B cells with an immunoregulatory phenotype. - Guadalupe Andreani; Michel Ouellet; Rym Menasria; Alejandro Martin Gomez; Corinne Barat; Michel J Tremblay (PLoS Neglected Tropical Diseases)
Visceral leishmaniasis is caused by the protozoan parasites Leishmania infantum and Leishmania donovani. This infection is characterized by an uncontrolled parasitization of internal organs which, when left untreated, leads to death. Disease progression is linked with the type of immune response generated and a strong correlation was found between disease progression and serum levels of the immunosuppressive cytokine IL-10. Other studies have suggested a role for B cells in the pathology of this parasitic infection and the recent identification of a B-cell population in humans with regulatory functions, which secretes large amounts of IL-10 following activation, have sparked our interest in the context of visceral leishmaniasis. We report here that incubation of human B cells with Leishmania infantum amastigotes resulted in upregulation of multiple cell surface activation markers and a dose-dependent secretion of IL-10. Conditioned media from B cells incubated with Leishmania infantum amastigotes were shown to strongly inhibit CD4(+) T-cell activation, proliferation and function (i.e. as monitored by TNF and IFNγ secretion). Blockade of IL-10 activity using a soluble IL-10 receptor restored only partially TNF and IFNγ production to control levels. The parasite-mediated IL-10 secretion was shown to rely on the activity of Syk, phosphatidylinositol-3 kinase and p38, as well as to require intracellular calcium mobilization. Cell sorting experiments allowed us to identify the IL-10-secreting B-cell subset (i.e. CD19(+)CD24(+)CD27(-)). In summary, exposure of human B cells to Leishmania infantum amastigotes triggers B cells with regulatory activities mediated in part by IL-10, which could favor parasite dissemination in the organism.